2015
DOI: 10.1111/nph.13389
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐biased gene expression in dioecious garden asparagus (Asparagus officinalis)

Abstract: SummarySex chromosomes have evolved independently in phylogenetically diverse flowering plant lineages. The genes governing sex determination in dioecious species remain unknown, but theory predicts that the linkage of genes influencing male and female function will spur the origin and early evolution of sex chromosomes. For example, in an XY system, the origin of an active Y may be spurred by the linkage of female suppressing and male promoting genes.Garden asparagus (Asparagus officinalis) serves as a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 71 publications
7
84
3
Order By: Relevance
“…The level of sex‐biased gene expression found in the S. viminalis reproductive tissue is markedly lower than that in animal species (Jiang & Machado, ; Pointer et al., ), consistent with the significantly higher degree of sexual dimorphism in animal systems. On the other hand, we found a larger percentage of sex‐biased genes compared to several plant and algae species with low levels of sexual dimorphism (Harkess et al., ; Lipinska et al., ; Zemp et al., ). This is indicative of higher intersexual morphological differences in the S. viminalis reproductive tissue, which is consistent with previous descriptions of the structural differences between male and female catkins (Cronk et al., ).…”
Section: Discussionmentioning
confidence: 65%
“…The level of sex‐biased gene expression found in the S. viminalis reproductive tissue is markedly lower than that in animal species (Jiang & Machado, ; Pointer et al., ), consistent with the significantly higher degree of sexual dimorphism in animal systems. On the other hand, we found a larger percentage of sex‐biased genes compared to several plant and algae species with low levels of sexual dimorphism (Harkess et al., ; Lipinska et al., ; Zemp et al., ). This is indicative of higher intersexual morphological differences in the S. viminalis reproductive tissue, which is consistent with previous descriptions of the structural differences between male and female catkins (Cronk et al., ).…”
Section: Discussionmentioning
confidence: 65%
“…The transcriptome assembly and translation for A. officinalis was taken from Harkess et al (2015) (http://datadryad.org/resource/doi:10.5061/dryad.92c6010.5061/dryad.92c60). We generated leaf RNA-Seq for A. asparagoides by first isolating total RNA from mature leaf tissue using a Qiagen RNeasy Plant Mini kit.…”
Section: Methodsmentioning
confidence: 99%
“…Male asparagus plants are comparatively more disease resistant, have better yields and live longer than female plants (Kabir 1993) and also they do not produce seeds to create 'asparagus weed problem'. According to Harkess et al (2015), the chromosome number of diploid asparagus is 2n = 20 with x = 10. The females, males and supermales have XX, XY and YY sex chromosomes, respectively, and specifically males as well as supermales possess genes involved in pollen microspore and tapetum development.…”
Section: Garden Asparagus (Asparagus Offcinalis L)mentioning
confidence: 99%
“…and C. grandis (L.) Voigt), kiwifruit (Actinidia deliciosa var. deliciosa) and hemp (C. sativa L.) homogametic female (XX) and heterogametic male (XY) plants were documented (Ming et al 2007;Cherif et al 2013) but, a recent study also reported supermales (YY) in asparagus (Harkess et al 2015). In papaya (Carica papaya), which is trioecious in nature due to availability of three sex types (male, female and hermaphrodite), XY system is available and two distinct Y chromosomes viz.…”
Section: Introductionmentioning
confidence: 99%